The effect of energy levels upon finishing zebu steers in feed lot - Salomoni, Eduardo; Von Tiesenhausen, Igor M.E.V.; Pereira, Euripedes Alves (Pesquisa Agropecuaria Brasileira, 2014)
Experimental animals were 36 steers of Guzerat breeding, weighing an average of 304 kilograms and varying from 18 to 24 months of age. They were randomly assigned to four ration treatments, the basic ration ingredients being ground corn, cottonseed meal, “gordura" (Meliris minutiflora) hay, corn silage, urea, and soybean oil. The rations were isonitrogenous (10% crude protein) with the following energy levels: Treatment 1 - 54% TDN, Treatment 2- 59%TDN, Treatment 3 - 65% TDN, and Treatment 4- 70% TDN. Treatment effects were determined on the basis of weight gain, yield of carcass and economic returns above feed cost. Mean daily weight gains in kilograms for the experiment were: 0.688; 0.804; 0.881 and 0.784 for Treatments 1, 2, 3 and 4, respectively. Differences were not significant. Treatments 1, 2, 3 and 4 were calculated to provide 86, 94, 104 and 112%, respectively, of the TDN requirements according to NRC recommendations. Average weight gains were approximately 63, 73, 80 and 71%, from those estimated for the levels of consumption during the experiment. Carcass yields for Treatments 1, 2, 3 and 4, respectively, were 56.3% (hot carcass) and 55.8% (cold carcass); the other yields of hot and cold carcass were 54.8 and 54.2; 53.8 and 53.3; 53.7 and 53.2. Yields for Treatment 1 were not significantly greater than in the others when corrected for equal slaughter weight. The addition of oil to the diets to increase the level of energy was not economically feasible.